Fault Detection and Fault-Tolerant Control for Nonlinear Systems - Li, Linlin; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2016)
Linlin Li addresses the analysis and design issues of observer-based FD and FTC for nonlinear systems. The author analyses the existence conditions for the nonlinear observer-based FD systems to gain a deeper insight into the construction of FD systems. Aided by the T-S fuzzy technique, she recommends different design schemes, among them the L_inf/L_2 type of FD systems. The derived FD and FTC approaches are verified by two benchmark processes. Contents Overview of FD and FTC Technology Configuration of Nonlinear Observer-Based FD Systems Design of L2 nonlinear Observer-Based FD Systems Design of Weighted Fuzzy Observer-Based FD Systems FTC Configurations for Nonlinear Systems< Application to Benchmark Processes Target Groups Researchers and students in the field of engineering with a focus on fault diagnosis and fault-tolerant control fields The Author Dr. Linlin Li completed her dissertation under the supervision of Prof. Steven X. Ding at the Faculty of Engineering, University of Duisburg-Essen, Germany.
Overview of FD and FTC Technology -- Configuration of Nonlinear Observer-Based FD Systems -- Design of L2 nonlinear Observer-Based FD Systems -- Design of Weighted Fuzzy Observer-Based FD Systems -- FTC Configurations for Nonlinear Systems -- Application to Benchmark Processes.
Keywords: Control engineering; Robotics; Automation; Electrical engineering; Environmental monitoring; Control, Robotics, Automation; Electrical and Electronic Engineering; Environmental Monitoring